Approach of location privacy protection based on order preserving encryption of the grid - Nan SHEN; Chun-fu JIA; Shuang LIANG; Rui-qi LI; Zhe-li LIU (Tongxin xuebao)
The centralized structure of the trusted third party is a major privacy protection structure on location based services.However,if the central third party server can not be trusted or compromised,users have the risk of leakage of privacy location.Aiming at the above problems,location privacy protection approach based on a user-defined grid to hide location was proposed.The system first automatically converted the query area into a user-defined grid,and then the approach utilized order preserving encryption,which made the user’s real-time position in the hidden state could still be compared.Because the information in the process of the approach was in a state of encryption,the server could not know the user’s location information,thus improved privacy protection of the user location.The central third party server only need to do simple comparison work,so its processing time overhead would effectively decrease.Security analysis certificate the security of the proposed approach and simulation experimental show the proposed approach can reduce the time cost of the central third party server.